Engineering the cytokinin-glucoside specificity of the maize β-D-glucosidase Zm-p60.1 using site-directed random mutagenesis - Filipi, Tomáš; Mazura, Pavel; Janda, Lubomír; Kiran, Nagavalli S; Brzobohatý, Břetislav (Phytochemistry, 2012)
The maize β-D-glucosidase Zm-p60.1 releases active cytokinins from their storage/transport forms, and its over-expression in tobacco disrupts zeatin metabolism. The role of the active-site microenvironment in fine-tuning Zm-p60.1 substrate specificity has been explored, particularly in the W373K mutant, using site-directed random mutagenesis to investigate the influence of amino acid changes around the 373 position. Two triple (P372T/W373K/M376L and P372S/W373K/M376L) and three double mutants (P372T/W373K, P372S/W373K and W373K/M376L) were prepared. Their catalytic parameters with two artificial substrates show tight interdependence between substrate catalysis and protein structure. P372T/W373K/M376L exhibited the most significant effect on natural substrate specificity: the ratio of hydrolysis of cis-zeatin-O-β-D-glucopyranoside versus the trans-zeatin-O-β-D-glucopyranoside shifted from 1.3 in wild-type to 9.4 in favor of the cis- isomer. The P372T and M376L mutations in P372T/W373K/M376L also significantly restored the hydrolytic velocity of the W373K mutant, up to 60% of wild-type velocity with cis-zeatin-O-β-D-glucopyranoside. These findings reveal complex relationships among amino acid residues that modulate substrate specificity and show the utility of site-directed random mutagenesis for changing and/or fine-tuning enzymes. Preferential cleavage of specific isomer-conjugates and the capacity to manipulate such preferences will allow the development of powerful tools for detailed probing and fine-tuning of cytokinin metabolism in planta.
Keywords: mutace; molekulární konformace; Glucosides; hydrolýza; vazebná místa; beta-glukosidasa; Substrate Specificity; glukosidy; sekvence aminokyselin; mutageneze cílená; Plant Proteins; Structure-Activity Relationship; beta-Glucosidase; Mutation; Amino Acid Sequence; Molecular Conformation; cytokininy; kukuřice setá; Cytokinins; rostlinné proteiny; Mutagenesis, Site-Directed; isomerie; rostlinné geny; Isomerism; Hydrolysis; Zea mays; zeatin; vztahy mezi strukturou a aktivitou; Amino Acids; substrátová specifita; Zeatin; aminokyseliny; Genes, Plant; Binding Sites